Listening and speaking competence in pre-technical English level of students at the Livestock Science Faculty of Universidad Técnica Estatal de Quevedo, Ecuador. - Varas Giler, Rosa Cecibel (2018)
The problem found in Universidad Técnica Estatal de Quevedo, was studied through a Case Study and an Action Research. The first part of the investigation is the Theoretical Framework where Methodology in EFL instruction; Definitions, Relevance, Types and Procedures of Listening and Speaking, their Relationship and Effects, and Attitudes towards these skills are expressed. The Literature Review provides information about Technology in English classes: Epistemological Foundation, Teachers´ Attitudes towards its use and Benefits for Students by using ICTs. Likewise, Multimedia was revised in order to define specific strategies. An Action Research methodology was employed to study the problem which is the lack of Listening and Speaking Skills on students of Agricultural Engineering, courses A-B of Livestock Science Faculty. This research contains information encompassing class observations and learners’ diagnostic evaluation and activity assessment. Checklists and corresponding results were used as data collection instrument for further analysis. After the analysis, it was concluded that English classes should have some modifications. Thus, a proposal was designed to accomplish this goal. It consists of the design of a Blended Learning System in EFL by using on line applications like Voicethread, Padlet, Discovery Education, and Masher. Formats and checklists were used to describe the objective and process of each strategy as well as an adapted evaluation instrument.